ANALISIS DETERMINAN NILAI PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER DI BURSA EFEK INDONESIA - Rivan Harfianto Putra (2022)
This research is a quantitative study to determine the effect of profitability as measured by ROE, leverage as measured by DER, and firm size as measured by SIZE on firm value as measured by PBV. In this study, companies in the primary consumer goods sector were used as research samples. Where the sample was selected through a purposive sampling technique, and as many as 40 companies in the primary consumer goods sector for the 2018-2020 period were used as research samples. Hypothesis testing in this study uses Panel Data Regression Analysis with the help of E-Views 12 software and the results in this study are (1) profitability has a significant effect on firm value, (2) leverage has no effect on firm value, (3) firm size has no effect on firm value.